Non-obstructive Coronary Artery Disease in Chinese Patients with Angina Diagnosed by Coronary Angiography: A Retrospective Study - Chengfei Peng; Shaoping Nie; Yingxian Sun; Hui Chen; Zuyi Yuan; Yanjun Gong; Xiaozeng Wang; Yaling Han; Xiaoxia Fu; Tianyu Xu (Cardiology Discovery)
Abstract. Objective:. This study aimed to estimate the proportion of non-obstructive coronary artery disease (CAD) patients in large percutaneous coronary intervention (PCI) centers in China. Methods:. The study was conducted at 6 large PCI centers in China from January 1, 2013 to December 31, 2015. Demographic and clinical data were collected from medical records, prescription records, and laboratory reports of patients with symptoms of angina who underwent coronary angiography (CAG). Results:. A total of 1713 patients were consecutively screened, 1600 of whom were included in the study. CAG showed that 300 patients had non-obstructive CAD while 1300 had obstructive CAD. Among the 300 patients with non-obstructive CAD, 203 displayed mild coronary stenosis (20%–49%) and 91 had normal coronary status (ie, <20% stenosis). Of the 1300 patients with obstructive CAD, 61.6% (801/1300) had typical symptoms of angina, compared with 49.3% (148/300) for patients with non-obstructive CAD. In addition, there were more women than men in the non-obstructive CAD group, whereas the reverse was observed among obstructive CAD patients. Conclusion:. The prevalence of non-obstructive CAD in the Chinese population with coronary heart disease was estimated to be approximately 20%. Additionally, typical angina symptoms were correlated with obstructive CAD, whereas female gender was identified as a risk factor for non-obstructive CAD.